(3OjhGf GdNhQi fjbhdGhS UGjZs - (3fjbhdGhS UGjZs ((3LHd dHfGf s)
(3ChdgG (B:s
(3cKQ GdYKGQ HYKQI GdQhSGA hNhi GdUZGQ HZQg GdcHQGA deG QCjJ GdQCS hgh egTe CjbfJ efg JgTe GdCYVGA s
(3BNQgG (B:s
(3hdcd HZi eUQY hdcd TQH eSQH hdcd ScQ UMhI hdcd cCS eTQH aGYd EPkG eG JHJZi MJi fQi ef jZdH s
(3HgG fXGe GdJYbjHIs
(3fSNJ SfI (B1830(3e TYQ Ojfi hZjQg efgG bUjOI egOGI ddCeQGA CHj GddeY YGe (B1725s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdhWfjI s
Keywords: (3GdCOHs